Africa’s Portrayal in African-American Writing - Neupane, Khagendra (Patan Gyansagar, 2024)
The depiction of Africa in African-American literature constitutes a nuanced and dynamic exploration, unveiling the intricate rapport between African-American writers and the African continent. Over centuries, Africa's portrayal has assumed myriad forms, serving as a symbolic homeland, a locus of struggle, and a wellspring of cultural inspiration. Imbued within these representations is a profound quest for identity and a yearning for belonging. Prestigious African-American authors, including Langston Hughes, Zora Neale Hurston, and Maya Angelou, adeptly interlace African culture, folklore, and history into the tapestry of their works. In so doing, they delve into themes of heritage, resilience, and cultural pride, presenting Africa not merely as a nostalgic ideal but as a vibrant tapestry of traditions intricately shaping the African-American experience. This representation transcends sentimentality, offering a palpable connection to ancestral roots and cultural heritage. Yet, the portrayal of Africa in African-American literature transcends idyllic visions of a distant homeland. Renowned authors such as Toni Morrison, Chinua Achebe, and Chimamanda Ngozi Adichie confront the harsh realities of colonization, slavery, and oppression in their narratives. In their hands, Africa becomes a complex terrain of struggle and resistance, where characters grapple with the enduring legacies of colonialism and the intricate dynamics of post-colonial identity. The representation of Africa in African-American literature reflects broader historical and political dynamics. During the Harlem Renaissance, there was a surge of interest in Pan-Africanism, as African-American writers actively sought connections with counterparts on the continent in the fight against racism and imperialism. This period witnessed an embrace of African art, literature, and culture, as writers sought to reclaim and celebrate their African heritage.